An Analysis of Content Operation Modes of Audio Platforms in the Digital Age—A Case Study of Ximalaya FM - Liu, Shurui (Journal of Linguistics and Communication Studies, 2025)
Taking Ximalaya FM as an example, this paper explores the content operation modes of audio platforms in the digital age. By analyzing the platform overview, content production and communication operation modes of Ximalaya FM, it reveals its innovative practices in diversified content, personalized recommendation, AIGC production mode, community interaction and commercialization paths. The study finds that Ximalaya FM has successfully enhanced user stickiness and brand influence through the diversified content production modes of UGC, PGC and PUGC, combined with data-driven optimization strategies and cross-border cooperation. However, the platform still faces problems such as content homogenization, review dilemmas and single interaction forms. In response to these issues, this paper puts forward suggestions such as strengthening the review mechanism, cultivating high-quality anchors and enriching interaction functions, in order to provide reference for the sustainable development of audio platforms.